2009
DOI: 10.1149/1.3139963
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Structural Degradation in a PEMFC Cathode Catalyst Layer: Carbon Corrosion

Abstract: In this study, the structural degradation of a polymer electrolyte membrane fuel cell (PEMFC) cathode catalyst layer due to carbon corrosion was investigated. To oxidize the catalyst carbon support, the PEMFC catalyst layer was subjected to a 30 h accelerated stress test that cycled the cathode potential from 0.1 to 1.5normalVRHE (where RHE denotes reversible hydrogen electrode) at 30 and 150 s intervals. Carbon dioxide release was measured in the gas exhaust to establish the rate and amount of carbon loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 28 publications
3
116
1
Order By: Relevance
“…Observed previously, 11 the CV and EIS Cdl measurements differed by a factor of 1 to 2. It is clarified here that the pseudo-capacitance part of the Pt oxide reduction peak may convolute the Cdl measured during CV.…”
Section: Observations Inmentioning
confidence: 61%
See 1 more Smart Citation
“…Observed previously, 11 the CV and EIS Cdl measurements differed by a factor of 1 to 2. It is clarified here that the pseudo-capacitance part of the Pt oxide reduction peak may convolute the Cdl measured during CV.…”
Section: Observations Inmentioning
confidence: 61%
“…The EIS spectra were fit to an equivalent circuit representing a transmission line network of the porous CL. As discussed elsewhere 11 in greater detail, the fitted parameters consisted of the high frequency cell resistance, the cathode CL protonic resistance, and the Cdl.…”
mentioning
confidence: 99%
“…The resulting spike in the cathode voltage to a potential of about 1.5 V vs. SHE produces severe corrosion of the carbon support material of the cathode catalyst, with associated damage by electrode layer thinning and disintegration, platinum nanoparticle agglomeration, and the loss of catalytically active platinum surface area. [6][7][8] Surface oxides may also form, making the cathode layer more hydrophilic and prone to water flooding, which drastically reduces oxygen access to active catalytic sites. 9 System control strategies have been sought to minimize these voltage spikes, but no practical solutions have emerged to eliminate the problem.…”
mentioning
confidence: 99%
“…Despite the majority of studies blaming voltage cycling of the cell for the carbon corrosion in PEMFC [184, 185, 187-189, 218, 243], some studies have associated its cause to the presence of liquid water in the catalyst [248][249][250][251][252]. Maass et al [249] found that the corrosion rate of carbon is linearly dependant on the molar water concentration.…”
Section: Corrosionmentioning
confidence: 99%